Agent-based simulation for a regional guarantee circle crisis. Issue 1 (2nd January 2022) - Tong, Ziqiang; Li, Pengxiang; Yang, Lei; Wang, Haonan
ABSTRACT: In view of the phenomenon of the guarantee network formed by the mutual guarantee of Chinese enterprises. First, the mechanism of crisis formation in regional guarantee circles is analysed through the network contagion effect, then the enterprise and guarantee model are constructed using the agent method. Second, the evolution rules of a regional guarantee circle crisis under different situations are designed. Finally, with the help of the Anylogic simulation software, the dynamic evolution process of the regional guarantee circle crisis "brewing-triggering-burst-diffusion" is realised. By simulating the contrast demonstration of the operation effect of the guarantee circle crisis in different situations, we find the network effect between the enterprise's individual behaviour and the guarantee circle crisis, and summarise the critical conditions that trigger the guarantee circle crisis and the general law of crisis diffusion, after which we propose the policy reasons and preventive measures arising from the guarantee circle crisis.